Reconfigurable assembly system design methodology for aerospace wing structures - Jefferson, Thomas G. (2017)
The aerospace industry is facing new challenges to meet burgeoning customer demand. An unprecedented number of orders for commercial aircraft has placed great urgency on aerospace manufacturers to make gains in production efficiency. Wing assembly is one such area where cycle times are in the order of hundreds of hours and commissioning cells can take several years which has led to a significant order backlog. In light of these challenges, new techniques are required to bring about greater agility to respond to market changes. Aerospace manufacturers must seize the opportunity to innovate and readdress approaches to ensure their prosperity. Recent research advocates Reconfigurable Assembly Systems (RAS) as a viable solution. A RAS is designed at the outset to change in structure to modify production capacity and functionality to meet new requirements. Yet, adding reconfigurability further increases design complexity. Despite the increased complexity, few formal methodologies exist to support RAS design for aerostructures.